Accelerated ageing reactions: towards simpler, solvent-free, low energy chemistry. Issue 18 (9th September 2020) - Huskić, Igor; Lennox, Cameron B.; Friščić, Tomislav
Abstract : Accelerated ageing reactions proceed spontaneously in mixtures of solid reactants, and provide a route towards developing solvent- and energy-free chemistry. Abstract : We provide an overview of chemical transformations that proceed spontaneously, by mixing of initially solid reactants, and are accelerated and/or directed through gentle stimuli in the form of mild heating, exposure to diverse gas or vapour environments, brief mechanical milling, and/or the presence of catalysts. This broad overview illustrates how such accelerated ageing (AA) reactions could provide a route to develop operationally simple, as well as safe, inexpensive and materials- and energy-efficient processes for the environmentally-friendly synthesis of diverse organic and metal–organic materials and molecules.